Thresholds and relations for soil‐hydraulic and soil‐physical properties as a function of burn severity 4 years after the 2011 Las Conchas Fire, New Mexico, USA. Issue 14 (20th June 2018) - Ebel, Brian A.; Romero, Orlando C.; Martin, Deborah A.
Abstract: Wildfire effects on soil‐physical and ‐hydraulic properties as a function of burn severity are poorly characterized, especially several years after wildfire. A stratified random sampling approach was used in 2015 to sample seven sites representing a spectrum of remotely sensed burn severity in the area impacted by the 2011 Las Conchas Fire in New Mexico, USA. Replicate samples from each site were analysed in the laboratory. Linear and linear indicator regression were used to assess thresholds in soil‐physical and ‐hydraulic properties and functional relations with remotely sensed burn severity. Significant thresholds were present for initial soil‐water content (θ i ) at 0–6 cm depth between the change in the Normalized Burn Ratio ( dNBR ) equal to 618–802, for bulk density (ρb ) at 3–6 cm between dNBR equal to 416–533, for gravel fraction at 0–1 cm between dNBR equal to 416–533, for fines (the silt + clay fraction) at 0–1 cm for dNBR equal to 416–533, and for fines at 3–6 cm for dNBR equal to 293–416. Significant linear relations with dNB R were present between ρb at 0–1 cm, loss on ignition (LOI) at 0–1 cm, gravel fraction at 0–1 cm, and the large organic fraction at 1–3 cm. No thresholds or effects on soil‐hydraulic properties of field‐saturated hydraulic conductivity or sorptivity were observed. These results suggest that ρb and LOI at 0–1 cm have residual direct impacts from the wildfire heat impulse. The θ i threshold is most likely from delayed groundcover/vegetation recovery that increases evaporation at the highest burn severity sites. Gravel and silt + clay thresholds at 0–1 cm at the transition to high burn severity suggest surface gravel lag development from hydraulic erosion. Thresholds in ρb from 3 to 6 cm and in silt + clay fraction from 3 to 6 cm appear to be the result of soil variability between sites rather than wildfire impacts. This work suggests that gravel‐rich soils may have increased resilience to sustained surface runoff generation and erosion following wildfire, with implications for assessments of postwildfire hydrologic and erosion recovery potential.